Effects of fishing on a temperate reef community in South Africa 2: benthic invertebrates and algae - Götz, A; Kerwath, S E; Attwood, C G; Sauer, W HH (African journal of marine science, 2009)
The effect of fishing on benthic reef communities was studied by comparing reefs within and outside the Goukamma Marine Protected Area (MPA) on the South African warm-temperate south coast. Although study sites were similar in terms of bathymetry and oceanographic conditions, benthic reef communities were significantly different with higher abundance of algae and crinoidea at fished sites. Crinoidea, the principal food source of roman Chrysoblephus laticeps, was scarce at protected sites where this species was most abundant. Low algal abundance at protected sites was negatively correlated with grazer abundance within the fish communities encountered there, suggesting a high potential for coexistence of these trophic guilds. Other fish species showed dietary overlap with roman, and their abundance was likely controlled by interspecific exploitative competition for food. The study suggests that a moderate rate of fishing can alter benthic communities through indirect effects on temperate reefs in South Africa.